OPTIMALISASI PEMANFAATAN PLATFORM MERDEKA MENGAJAR SEBAGAI SARANA PENGUATAN KOMPETENSI GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA - Salsinha, Cecilia Novianti; Bete, Hendrika; Bone, Dominifridus; Solo, Prudensius Manek Maria Fransiska Venidora; Nifu, Martha Marsela; Kasa, Andreas Roberto; Timutang, Moses (Universitas Mataram, 2024)
Introduction (background): One of the government's steps to restore learning due to the Covid 19 pandemic is to issue a policy on the use of the Independent Learning Curriculum (KMB). However, in its implementation, schools are given the freedom to implement the curriculum in accordance with school conditions. St. Aloysius Niki-Niki Catholic Private Junior High School is in the IKM Mandiri Belajar category. This shows that KMB implementation has not been optimal. This is because this platform has only been used by schools since August 2022. In addition, schools are constrained by the categorization given which limits the school's space to implement KMB. Purpose of activities: One way that can be used to accelerate SMIs is to maximize the use of PMM. PMM comes with a high-tech approach that can help teachers in obtaining references, inspiration, understanding, and training independently to implement the Independent Curriculum. Method of activity: Pengabdi optimizes the use of PMM to teachers by providing training on the use of PMM. This activity was attended by the Principal and 19 teachers. In addition to providing guidance containing PMM, the service team also provides questionnaires at the end of activities as part of feedback on service activities. Results of activities: PMM optimization activities are also considered very interesting because 80% of teachers are new to this kind of training, even though 60% of teachers take a long time to explore PMM. This is due to the unstable internet network and teachers are not used to using this platform. However, the results of the St. Aloysius Niki-Niki Catholic Junior High School Education report card also provide promising results regarding teacher participation in the use of PMM where the participation rate in 2022 is 10, increasing by 622% in 2023 to 72.2. This makes this school in the top ranking category at the Regency / City level and in the upper middle category nationally. Conclusion: This kind of mentoring activity for teachers is very necessary considering that teachers also need additional insight and sharing experiences about IKM. The teachers have also committed to continue to optimize the use of PMM and will change the status of SMIs to Mandiri Change, in 2024.